Kinetika Adsorpsi Ion Besi (II) Oleh Biomassa Chaetoceros sp. - Widyawati, Paini Sri (Universitas Atma Jaya Yogyakarta, 2006)
This research was done to study the adsorption kinetic of ferrous ionic by Chaetoceros sp. Many variables influenced the adsorption capacity of absorbent on ferrous ionic including interaction time, ferrous ionic concentration and pH. Two absorbens were used in this study i.e. pure culture and natural spoiled product called Diatomite/ Diatomae earth / Diatomaceous earth / Diatomooze of Chaetoceros sp. biomass. The adsorption capacity by biomass was measured by atomic absorption spectrophotometry method (AAS). The result showed that the adsorption process of two absorbents happened very fast. The time needed to get maximal adsorption were 10 and 15 minutes respectively. Adsorption pattern of two biomass can be interpreted by Langmuir and Freundlich isoterm showing monolayer. The adsorption capacity of Diatomite was five times higher than that of the pure culture biomass because it was influenced by surface group charge and wide surface area of porous. Acidity degree (pH) of solution determined surface active group charge and solubility of iron (II). The increased pH value, the biomass adsorption capacity was added because surface active group had negative charge. The adsorption of biomass was maximal around pH 5 while for pH higher than 5, it wasn’t significantly increased because the iron (II) formed insoluble hydroxide compound.